(untitled) (Journal of Informatics Education and Research, 2025)
This study aims to present Tesla’s experience in utilizing artificial intelligence to achieve sustainable development, by integrating AI into areas such as autonomous driving, solar energy management, and battery performance optimization. Through these efforts, Tesla has achieved tangible results that contribute to the realization of several Sustainable Development Goals, including Goal 7 (Affordable and Clean Energy), Goal 11 (Sustainable Cities and Communities), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action).